Comparative in vitro/in situ approaches to three biomarker responses of Myriophyllum alterniflorum exposed to metal stress. (May 2019) - Decou, Raphaël; Bigot, Servane; Hourdin, Philippe; Delmail, David; Labrousse, Pascal
Abstract: Surface water pollution by trace metal elements constitutes problems for both public and terrestrial/aquatic ecosystem health. Myriophyllum alterniflorum (alternate watermilfoil), an aquatic macrophyte known for bioaccumulating this type of pollutant, is an attractive species for plant biomonitoring within the scope of environmental research. The two metal elements copper (Cu) and cadmium (Cd) are considered in the present study. Cu is essential for plant development at low concentrations, while very high Cu concentrations are detrimental or even lethal to most plants. On the other hand, Cd is usually toxic even at low concentrations since it adversely affects the physiological plant functions. In order to check whether watermilfoil could be used for the in situ biomonitoring of Cu or Cd pollution in rivers, the plant biomarker sensitivity is first tested during long-term in vitro assays. Three markers specific to oxidative stress (glucose-6-phosphate dehydrogenase, malondialdehyde and α-tocopherol) are evaluated by varying the pollutant concentration levels. Given the absence of effective correlations between Cu and all biomarkers, the response profiles actually reveal a dependency between Cd concentration and malondialdehyde or α-tocopherol biomarkers. Conversely, preliminary in situ assays performed at 14 different localities demonstrate some clear correlations between all biomarkers and Cu, whereas the scarcity of Cd-contaminated rivers prevents using the statistical data. Consequently, the three indicated biomarkers appear to be effective for purposes of metal exposure analyses; moreover, the in situ approach, although preliminary, proves to be paramount in developing water biomonitoring bases. Highlights: Watermilfoil is evaluated through biomarkers for its use in water quality monitoring. G6PDH, MDA and VitE biomarkers are not correlated with in vitro Cu exposures. Only MDA and VitE biomarkers are correlated to Cd concentration in vitro. Interestingly, correlations between freshwater [Cu] and all biomarkers are evidenced. Other field parameters need to be considered for the evaluation of this plant model.